2016
DOI: 10.1080/10438599.2016.1202514
|View full text |Cite
|
Sign up to set email alerts
|

Incorporating innovation subsidies in the CDM framework: empirical evidence from Belgium

Abstract: Die Dis cus si on Pape rs die nen einer mög lichst schnel len Ver brei tung von neue ren For schungs arbei ten des ZEW. Die Bei trä ge lie gen in allei ni ger Ver ant wor tung der Auto ren und stel len nicht not wen di ger wei se die Mei nung des ZEW dar.Dis cus si on Papers are inten ded to make results of ZEW research prompt ly avai la ble to other eco no mists in order to encou ra ge dis cus si on and sug gesti ons for revi si ons. The aut hors are sole ly respon si ble for the con tents which do not neces … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
16
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 39 publications
1
16
0
1
Order By: Relevance
“…We use panel data on manufacturing firms from three waves of the Innovation Surveys carried out in these countries (referring to the years 2004, 2006 and 2008 respectively). The study estimates additionality effects of R&D tax credits in each of these economies by using a three-step estimation procedure previously employed by Czarnitzki and Hussinger (2004) and Cerulli and Poti (2012) (see also Czarnitzki and Delanote, 2014). In a nutshell, our results suggest that firms in industries with high R&D orientation (and in particular in science-based and specialized suppliers) are on average more responsive to fiscal incentives to R&D, especially in using these incentives and in increasing their R&D expenditures.…”
Section: Introductionmentioning
confidence: 78%
See 1 more Smart Citation
“…We use panel data on manufacturing firms from three waves of the Innovation Surveys carried out in these countries (referring to the years 2004, 2006 and 2008 respectively). The study estimates additionality effects of R&D tax credits in each of these economies by using a three-step estimation procedure previously employed by Czarnitzki and Hussinger (2004) and Cerulli and Poti (2012) (see also Czarnitzki and Delanote, 2014). In a nutshell, our results suggest that firms in industries with high R&D orientation (and in particular in science-based and specialized suppliers) are on average more responsive to fiscal incentives to R&D, especially in using these incentives and in increasing their R&D expenditures.…”
Section: Introductionmentioning
confidence: 78%
“…The source of HHI data is the Micro-Dyn database, available at: http://www.micro-dyn.eu.9 Cerulli and Poti (2012: 31) also adopted a similar procedure in their analysis of input and output additionality of the Italian R&D policy scheme FAR. See alsoCzarnitzki and Delanote (2014) for a recent overview of this type of modeling approach.…”
mentioning
confidence: 99%
“…Czarnitzki and Lopes‐Bento (2014) found that the subsidy has a positive impact on patenting in Germany. Similarly, Czarnitzki and Delanote (2017) found a positive effect of R&D subsidies on innovation output in Belgium, using the CDM model 3 . Bronzini and Piselli (2016) found that innovation incentive has a significant impact on the number of patent applications, especially in the case of smaller firms.…”
Section: Effectiveness Of Fiscal Incentives On Innovationmentioning
confidence: 85%
“… The Crépon–Duguet–Mairesse (CDM) model is a framework for estimatingo the knowledge production function (see Czarnitzki & Delanote, 2017). …”
mentioning
confidence: 99%
“…Although we do not fully understand this phenomenon, we believe this could be caused by the way we measure revenues (new to the firm), and possibly, is non-observed additionality on new to the market revenues, that is, the weighted complement of our measure. The fact that we cannot find any output additionalities lead us to look for other ways to measure these type of impacts, and the CDM model (Crepon, Duguet, & Mairessec, 1998), could be a right approach in the case of productivity increase related to subsidies, even when recent literature point out to a negative result in this field (Czarnitzki & Delanote, 2017).…”
Section: Discussionmentioning
confidence: 99%